TRAINING OPERATION AND MAINTENANCE OF FETAL DOPPLER TO MAINTAIN THE HEALTH OF MOTHERS AND CHILDREN AT THE COMMUNITY HEALTH CENTER IN THE SOUTH KREMBANGAN, SURABAYA: TRAINING OPERATION AND MAINTENANCE OF FETAL DOPPLER TO MAINTAIN THE HEALTH OF MOTHERS AND CHILDREN AT THE COMMUNITY HEALTH CENTER IN THE SOUTH KREMBANGAN, SURABAYA - Ridha Makruf, Muhammad; Pudji, Andjar (Frontiers in Community Service and Empowerment, 2025)
This community service activity focuses on counseling and training related to the operation and maintenance of fetal Doppler devices as an effort to improve maternal and child health services in the South Krembangan Village area, Surabaya. Fetal Doppler is a critical medical device used to monitor fetal heart rate and ensure the well-being of the fetus during pregnancy. However, its effectiveness greatly depends on the users' knowledge and skills, particularly among midwives and health workers at Community Health Centers (Puskesmas). The activity involved structured training sessions combining theoretical explanations and practical demonstrations, aiming to enhance participants’ understanding of safe device operation, routine maintenance procedures, and early detection of equipment malfunctions. The results showed increased competency among participants in both operating the device and performing basic troubleshooting. This initiative not only supports the continuity of quality antenatal care but also strengthens local health capacity in the effort to reduce maternal and infant morbidity and mortality. Continuous follow-up and evaluation are recommended to sustain the impact of the program.